2017
DOI: 10.2527/jas.2016.0411
|View full text |Cite
|
Sign up to set email alerts
|

Performance, intestinal microflora, and amino acid digestibility altered by exogenous enzymes in broilers fed wheat- or sorghum-based diets

Abstract: The objective of the current study was to compare the effects of dietary enzymes and nutrient restriction on performance and bone mineralization in birds fed wheat- or sorghum-based diets. A total of 720 d-old male broiler chicks were randomly allocated to 8 treatments, with 6 replicates per treatment and 15 birds per replicate. Birds were reared in floor pens from 0 to 35 d. The study used a 2 × 4 factorial arrangement with 2 grains (sorghum or wheat) and 4 diets: positive control (no enzyme and ME, digestibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the selection of articles, the enzymes of interest in poultry were phytase or glucanases in combination with xylanases [ 47 , 51 , 53 , 54 , 55 ]. Glucanase combined with xylanase did not induce an improvement in body weight, feed intake or FCR, which was partly explained by the absence of modulation of the structure of the intestinal villi [ 47 , 51 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the selection of articles, the enzymes of interest in poultry were phytase or glucanases in combination with xylanases [ 47 , 51 , 53 , 54 , 55 ]. Glucanase combined with xylanase did not induce an improvement in body weight, feed intake or FCR, which was partly explained by the absence of modulation of the structure of the intestinal villi [ 47 , 51 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucanase combined with xylanase did not induce an improvement in body weight, feed intake or FCR, which was partly explained by the absence of modulation of the structure of the intestinal villi [ 47 , 51 , 54 ]. However, phytase induced an increase in body weight gain [ 53 , 55 ]. Most studies showed that enzymes had no effect on the abundance of lactic-acid-producing bacteria or even on intestinal and caecal pH [ 47 , 51 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, dietary treatments failed to modify the overall diversity of cecal microbiota at 21 and 42 d. These results were consistent with previous reports. Current research indicates that supplementation with BS [ 91 ], FOS, MOS [ 40 ], SB [ 92 ], MAN [ 93 ], and PT [ 94 ] has no effect on the diversity and community structure of cecal microbiota in broilers. In fact, aging has a greater impact on microbiota than that of therapy [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dietary treatments failed to modify the overall diversity of cecal microbiota at 21 and 42 d. These results were consistent with previous reports. Current research indicates that supplementation with BS [76], FOS, MOS [23], SB [77], MAN [78], and PT [79] has no effect on the diversity and community structure of cecal microbiota in broilers. In fact, aging has a greater impact on microbiota than that of therapy [80].…”
Section: Discussionmentioning
confidence: 99%